Toxicity of ceramic nanoparticles in human alveolar epithelial A549 cells at air-liquid interface - Fraga, Sónia (2019)
Several ceramic industries have already incorporated within their production processes the manufacture of different types of ceramic nanoparticles (NPs), as well as the application of those nanomaterials on conventional products, which increases the risk of human exposure to these nanoparticles, particularly in occupational settings. The aim of this study was to investigate the in vitro toxicity of ceramic NPs (ZrO2, CeO2 and Sb2O3•SnO2 NPs) in human alveolar epithelial cells, a primary target following inhalation exposure.